Favourite Sounds: the Australian music field. Issue 1 (May 2018) - Dibley, Ben; Gayo, Modesto
Drawing on data from the Australian Cultural Fields survey, this article investigates the music field. Following the protocols of multiple correspondence analysis (MCA), it charts the music field in Australia, mapping the cultural and social contours of those who populate this space. In this context, the article considers the notion of emerging cultural capital deployed in recent surveys on social class. The article questions the contention that the correlation between emergent cultural practices and a younger educated cohort necessitates a new class formation by returning to Bourdieu's arguments on the connections between cultural capital, age and the relations between class fractions.